Assessing the Effects of Healthy and Neuropathological Aging on Personality with the Iowa Scales of Personality Change. Issue 5 (4th July 2021) - Zirbes, Christian; Jones, Andrew; Manzel, Kenneth; Denburg, Natalie; Barrash, Joseph
ABSTRACT: Personality changes in older adults with brain disease may be confounded by effects of normal aging. In this cross-sectional study, ratings with the Iowa Scales of Personality Change for 62 healthy older adults (OA-H, aged 60+) were compared to matched older adults with brain diseases (OA-BD). OA-H did not show any significant personality changes from middle age to older adulthood. However, between 10% and 20% of OA-H developed a disturbance in Lack of Stamina, Inflexibility, Lability, and Lack of Insight . Otherwise, the pattern of findings suggesting normal aging effects on personality disturbances in clinical groups are generally minimal.